Diagnostic delay and survival in high-grade gliomas – evidence of the 'waiting time paradox'?. (4th July 2015) - Aggarwal, Ajay; Herz, Naomi; Campbell, Philip; Arkush, Leo; Short, Susan; Rees, Jeremy
Abstract: Introduction. We present a retrospective single-centre study to determine whether delays in diagnosis of high-grade glioma (HGG) impact on overall survival (OS). Material and methods. Consecutive patients diagnosed with HGG at a single neuroscience centre in 2011 were reviewed. Route of referral and time from initial presentation to diagnosis were analysed and correlated with OS. Results. 118 patients were studied – 92 patients with glioblastoma (GBM). Diagnosis of GBM in patients presenting to emergency services was quicker than that through outpatients (8 days vs. 26 days, p < 0.0001), but these patients had significantly worse OS (181 days vs. 386 days p = 0.0075). This trend was observed for the whole cohort (Grade III and GBM), with OS 278 days in patients presenting to emergency services compared with 423 days for patients presenting via outpatients (p = 0.0034). Patients presenting to outpatients were younger (median age: 54 years) compared with patients presenting to emergency services (median age: 62.5 years) (p = 0.0106). There were no other differences between the two groups with respect to the nature of presenting symptoms. Conclusion. Earlier diagnosis is paradoxically associated with a worse OS in GBM. An 'aggressive' phenotype with rapid symptomatic deterioration and hence emergency presentation is a poor prognostic factor not influenced by earlier diagnosis.